Observations on Food Consumption and Preference in Four Alaskan Mammals - Morrison, Peter R.; Teitz, William J. (ARCTIC, 1953)
Contains report of a study made during Oct.-Nov. in Wisconsin where animals captured two months earlier in Alaska, were maintained in captivity. Alaskan ground squirrels, Dawson red-back voles, Alaskan collared lemmings and pikas were fed both fresh and dry food and their water intake, caloric intake and food preferences studied. There was little agreement among the various species in food preference; caloric intake was in general greater per weight unit in small than in large animals. Simple food consumption values are shown to be a fairly reliable measure of metabolic requirements and output in wild animals. The lemmings' catholic taste is noted as a factor favorable for survival in rigorous environment. For other papers from this study see Arctic Bibliography No. 26500-26501.